2016
DOI: 10.1080/17445647.2016.1152920
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor integrity of the Mar Piccolo Basin (Southern Italy): quantifying anthropogenic impact

Abstract: The Mar Piccolo Basin is a coastal brackish marine ecosystem located along the northern coast of the Gulf of Taranto (Southern Italy). Despite the ecological relevance of the area (Site of Community Importance IT9130004, Regional Reserve 'Palude La Vela' EUAP1189), the entire basin is subjected to intensive human usage. The main activities include extensive mussel farming, important industrial activities, a military harbor and densely populated shores. The goal of our study was to spatially quantify human pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In fact, the short-lived non-feeding larvae do not usually disperse very far (Svane & Young, 1989) so a new finding in distant localities is usually symptomatic of human-mediated transport. The two localities where S. brakenhielmi has been found (Olbia and Taranto) are both strongly affected by anthropogenic activities, such as industrial activities, intense naval traffic and large mussel farms (Cardellicchio et al, 1991;Bracchi et al, 2016;Marchini et al, 2016;Tursi et al, 2018). Indeed, the areas surrounding Olbia and Taranto are considered Italian hotspots of alien species introduction (Cecere et al, 2016;Marchini et al, 2013;Mastrototaro et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the short-lived non-feeding larvae do not usually disperse very far (Svane & Young, 1989) so a new finding in distant localities is usually symptomatic of human-mediated transport. The two localities where S. brakenhielmi has been found (Olbia and Taranto) are both strongly affected by anthropogenic activities, such as industrial activities, intense naval traffic and large mussel farms (Cardellicchio et al, 1991;Bracchi et al, 2016;Marchini et al, 2016;Tursi et al, 2018). Indeed, the areas surrounding Olbia and Taranto are considered Italian hotspots of alien species introduction (Cecere et al, 2016;Marchini et al, 2013;Mastrototaro et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This study reports the presence of S. brakenhielmi in the western and central Mediterranean Sea, in particular along the North-eastern coasts of Sardinia (Olbia, Western Tyrrhenian Sea) and in the Mar Piccolo basin (Gulf of Taranto, Northern Ionian Sea). Both finding areas are strongly influenced by human activities and pressures (Bracchi et al, 2016;Tursi et al, 2018), such as high maritime traffic, commercial shipping and import/export of living marine species for aquaculture, considered the most important pathways for the introduction of the alien species. Therefore, a hypothesis on the most likely vector of introduction of this non-indigenous species in the western Mediterranean basin is suggested.…”
Section: Introductionmentioning
confidence: 99%
“…A small reef and a ruined stone pier, together with a few scattered stones and mussel shells, are the only natural hard substrata. Recent observations both in situ and by remote sensing showed that the anthropogenic impact on the Mar Piccolo is very high in the First Inlet but less severe in the Second Inlet and arises mainly from lines, poles and frames used for mussel farming (Bracchi et al 2016). Hydrodynamism is limited, as is exchange with the adjacent Mar Grande basin (i.e.…”
Section: Study Sitementioning
confidence: 99%
“…However, we expect that the true spatial extent of physical disturbance related to anthropogenic activities is likely to be even more extensive than estimated in this study as the physical anthropogenic footprint measured using the multibeam bathymetric data only captures seabed features observable in the 2 m resolution data (i.e., > 2 × 2 pixels or 4 × 4 m). Furthermore, the extent of anthropogenic influence on shallow marine zones extends well beyond physical disturbance to the seabed, and can include chemical pollution (Aksu et al, 1998;Coskun et al, 2016), marine litter (Ramirez-Llodra et al, 2013), changes in sedimentation (Kerner, 2007;Anthony et al, 2014;Paradis et al, 2018) and to the composition of sediments (Syvitski et al, 2005), and modifications and eradication of benthic habitats (Erftemeijer and Lewis, 2006;Bracchi et al, 2016;Lastras et al, 2016;Ribó et al, in review). Further research assessing the impact of human activities beyond the physical footprint (e.g., chemical, and biological) is necessary to fully understand the influence humans are having in the shallow marine realm.…”
Section: The Physical Human Footprintmentioning
confidence: 99%